Structural and functional dissection of the interplay between lipid and Notch binding by human Notch ligands. (1st June 2017) - Suckling, Richard J; Korona, Boguslawa; Whiteman, Pat; Chillakuri, Chandramouli; Holt, Laurie; Handford, Penny A; Lea, Susan M
Abstract: Recent data have expanded our understanding of Notch signalling by identifying a C2 domain at the N‐terminus of Notch ligands, which has both lipid‐ and receptor‐binding properties. We present novel structures of human ligands Jagged2 and Delta‐like4 and human Notch2, together with functional assays, which suggest that ligand‐mediated coupling of membrane recognition and Notch binding is likely to be critical in establishing the optimal context for Notch signalling. Comparisons between the Jagged and Delta family show a huge diversity in the structures of the loops at the apex of the C2 domain implicated in membrane recognition and Jagged1 missense mutations, which affect these loops and are associated with extrahepatic biliary atresia, lead to a loss of membrane recognition, but do not alter Notch binding. Taken together, these data suggest that C2 domain binding to membranes is an important element in tuning ligand‐dependent Notch signalling in different physiological contexts. Synopsis: Notch ligands possess variable lipid‐binding domains that mediate interaction with membranes of diverse lipid composition. A complex formation between Notch ligands, membrane lipids and Notch is required for efficient Notch signalling, and is disrupted in Jagged1 mutations associated with extrahepatic biliary atresia. New crystal structures for human Notch ligands Jagged2 and Delta‐like4 show variation in the ligand C2 domain lipid‐binding region, which is reflected by their binding preferences to liposomes of different compositions. Liposomes show enhanced binding to most ligands in the presence of Notch, suggesting a crosstalk between lipid and Notch binding. Selective loss of membrane binding appears to underlie defective Notch activation associated with a subset of Jagged1 C2 domain disease‐causing variants. The data suggest an important role for membrane binding in fine‐tuning the Notch signal in specific physiological contexts. Abstract : Structural variability in the C2 domain of Notch ligands determines membrane binding and regulates Notch activation, a role that is lost in disease‐associated Jagged1 variants.